Особенности размножения клопа вредной черепашки (Eurigaster integriceps Put.) - Тарануха, М. Д. (Вестник зоологии, 1970)
The article deals with the problem on type, duration and frequency of E.integriceps mating and on the peculiarities and frequency of oviposition by fertilized and non-fer-tilized females.
It is established that there is a direct dependence between the quantity of laid eggs and duration of the female life. The morpho-functional investigation of the females, the cycle of the development of which was finished, showed that the formation of eggs in them has already stopped.
The mating of E.integriceps is a very stable and long process (9—15 hrs). Fertilization of females and oviposition can be momentary and multiple. Semen, introduced by the male during copulation is preserved in seminal receptacle of the female for a long time, that permits it to lay fertilized eggs many times.
A trust-worthy dependence of the quantity of laid eggs on the female weight was not established.